2016
DOI: 10.1016/j.joi.2016.04.017
|View full text |Cite
|
Sign up to set email alerts
|

A new methodology for comparing Google Scholar and Scopus

Abstract: A new methodology is proposed for comparing Google Scholar (GS) with other citation indexes. It focuses on the coverage and citation impact of sources, indexing speed, and data quality, including the effect of duplicate citation counts. The method compares GS with Elsevier's Scopus, and is applied to a limited set of articles published in 12 journals from six subject fields, so that its findings cannot be generalized to all journals or fields. The study is exploratory, and hypothesis generating rather than hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 32 publications
6
78
0
6
Order By: Relevance
“…Since Spearman coefficient (ρ) is independent of the normality of the data distribution and moreover it can handle ties, in this study has been used Spearman ρ coefficient for the construction of the correlation matrix. 41,9 The correlation matrix (12×12) was formulated and most indicators were found to be significantly correlated (Spearman ρ > 0.8) with each other at a statistical significance level of 0.05, but there were also a few indicators that showed no strong correlation (ρ < 0.5) with the majority of other indicators. Table 5 shows that, the Spearman's ρ correlation coefficient between JCRIF and AIF (after removing self-citations) reaches a statistical significance level with a high correlation, ρ = 0.96.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Spearman coefficient (ρ) is independent of the normality of the data distribution and moreover it can handle ties, in this study has been used Spearman ρ coefficient for the construction of the correlation matrix. 41,9 The correlation matrix (12×12) was formulated and most indicators were found to be significantly correlated (Spearman ρ > 0.8) with each other at a statistical significance level of 0.05, but there were also a few indicators that showed no strong correlation (ρ < 0.5) with the majority of other indicators. Table 5 shows that, the Spearman's ρ correlation coefficient between JCRIF and AIF (after removing self-citations) reaches a statistical significance level with a high correlation, ρ = 0.96.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand how these indicators differ from each other, and the degree of their validity. 8,9 The Eigen factor explicitly excludes journal self-citations unlike most other indicators. 10 Reviews the literature on citation impact indicators.…”
mentioning
confidence: 99%
“…The authors analysed 982 articles, concluding that only 6.1% of them (60) had duplicate versions, which was taken to mean that they were documents that the system had not merged. Moed et al (2016) also indicated that duplicates, in the strict sense (with identical metadata), were rare (0.2%) in their study of a limited set of articles (1200) published in 12 journals. Even so, this percentage depends on the document type analysed, increasing significantly in the case of monographs.…”
Section: A) Matching Versionsmentioning
confidence: 99%
“…This may have been due to the fact that the team at the beginning was made up of only two people (OrdunaMalea et al, 2016). In fact, some of the limitations or criticisms that it received in its early days, such as coverage and speed of indexation (Jacsó, 2005a), were later transformed into strengths (Moed et al, 2016;Thelwall and Kousha, 2017, in press). …”
Section: The Evolution Of An -Already Old -Debatementioning
confidence: 99%
See 1 more Smart Citation